A moderation of star rating on the correlation between integrated strategies and organizational performance: A proposed framework - Saad, Shahrin; Yahya, Khulida Kirana; Pangil, Faizuniah (2010)
Organizational Performance has been a well-liked discussion topic among business researchers. This is due to the conflict of objectives in measuring the performance. Although performance depends very much on its objectives but researchers are also concern on the strategy to be implemented in ensuring of achieving the performance. There are varies of business strategies have been discussed. This research is attempting to integrate strategies by different business gurus and incorporate them with human resource approach in achieving a single strategy dimension and it will be tested the correlation with organizational performance On top of that, this research also is proposing to compare the different level of hotel star rating and how does it influence the strategy uses in the correlation to the performance.